Low Incubation Temperature During Late Incubation and Early Feeding Affect Broiler Resilience to Necrotic Enteritis in Later Life - Wijnen, Hendrikus J.; van der Pol, Carla W.; van Roovert-Reijrink, Inge A. M.; De Smet, Joren; Lammers, Aart; Kemp, Bas; van den Brand, Henry; Molenaar, Roos (Frontiers in Veterinary Science, 2021)
Resilient animals can cope with environmental disturbances in life with minimal loss of function. Resilience can be enhanced by optimizing early-life conditions. In poultry, eggshell temperature (EST) during incubation and early feeding are two early-life conditions that are found to alter neonatal chick quality as well as immune response in later life. However, whether these early-life conditions affect disease resilience of chickens at later ages has never been studied yet. Hence, we studied the effects of EST [(37.8°C (control) or 36.7°C (lower)] during late incubation (≥embryonic days 17–19.5) and feeding strategy after hatch [immediately (early feeding) or 51–54 h delayed (delayed feeding)] on later-life broiler resilience in a 2 × 2 factorial arrangement. At hatch, 960 broilers of both sexes from a 54-week-old Ross breeder flock were equally divided over 32 pens (eight replicate pens per treatment combination) and grown for 6 weeks. Necrotic enteritis was induced by a single inoculation of Eimeria spp. at d 21 and repeated Clostridium perfringens inoculation (3×/d) during d 21–25. Mortality and body weight (BW) gain were measured daily during d 21–35 as indicators of resilience. Additionally, disease morbidity was assessed (gut lesions, dysbacteriosis, shedding of oocysts, footpad dermatitis, and natural antibody levels in blood). Results showed a lack of interaction between EST and feeding strategy for the vast majority of the variables. A lower EST resulted in lower BW gain at d 5 and 8 post Eimeria inoculation (P = 0.02) and more Eimeria maxima oocysts in feces at d 8 post Eimeria inoculation compared to control EST (P < 0.01). Early feeding tended to lower mortality compared to delayed feeding (P = 0.06), but BW gain was not affected by feeding strategy. Morbidity characteristics were hardly affected by EST or feeding strategy. In conclusion, a few indications were found that a lower EST during late incubation as well as delayed feeding after hatch may each impair later-life resilience to necrotic enteritis. However, these findings were not manifested consistently in all parameters that were measured, and conclusions are drawn with some restraint.